Effectiveness between two tooth brushing methods on removing dental plaque - Giri, Dhirendra Kumar (Journal of Nobel Medical College, 2018)
Background: Biofilm usually is a group of micro-organisms in which bacterial cells adhere to each other. It may form on a living or non-living surfaces within a self-produced matrix of glycocalx. Recently, plaque has been identified as a biofilm, and its structure, microbiology and patho-physiology have been described. The effectiveness between modified bass technique and normal brushing technique has been compared in this study. Material & Methods: Sixty auxiliary workers working in Nobel Medical College and Teaching Hospital were selected using systematic random sampling technique. Plaque accumulation was assessed on the index teeth using Silness and Loe plaque index. Both normal tooth brushing practices and modified Bass technique were asked to perform using a standard tooth brush and fluoridated dentifrices without label was used for all the subjects after the morning breakfast. The difference of the PI scores recorded in different examinations was assessed using ANCOVA test. Results: The mean PI score was found similar for normal brushing and modified bass technique at the base line examination (P<0.05). The modified Bass technique was more effective in removing plaque than normal tooth brushing (P<0.05) Conclusion: Tooth brushing is the most common, easy and effective method of plaque control. At the same time tooth brushing with correct technique reduces plaque effectively and maintains the integrity of tooth and surrounding periodontium. Modified Bass technique plays a vital role in prevention of plaque control, dental caries and periodontal disease. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 26-29